METHODOLOGY FOR AUTOMATIC DETERMINATION OF CONTRAST OF LASER MARKING FOR DIFFERENT MATERIALS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
A new methodology for determining and optimizing the contrast of the technological laser marking process has been developed. It can evaluate the quality of the markings regardless of the type of material and the type of laser system. To perform the test analysis, a specialized test field is programmed, which including the change of two of the main parameters influencing the marking process: the linear energy density (LED) and the linear density of the pulses (LDI). Marking of a test field consisting of squares of a certain size is done by means of a raster marking method with a constant step between the lines. The results are processed with a digital camera and specialized software. The maximum blackening is compared with the background of all fields and is juxtaposed with the effective energy needed to obtain a certain contrast. Several consecutive iterations are made, with each of the following experiments excluding the variants with least contrast. Thus, the study consistently brings the result to a minimum working area of the basic technological parameters, providing the user's desired contrast of the marking. The developed author's method of automatically determining the contrast of the laser marking reduces the time for preliminary experimental research and gives a reliable and subjectively absent way of qualitatively marking different types of industrial products.